2017
DOI: 10.1310/sci2303-271
|View full text |Cite
|
Sign up to set email alerts
|

Economic Consequences of an Implanted Neuroprosthesis in Subjects with Spinal Cord Injury for Restoration of an Effective Cough

Abstract: To determine if an implanted neuroprosthesis for restoration of an effective cough is less costly than conventional methods of respiratory management. Nonrandomized clinical trial of participants ( = 14) with spinal cord injury (SCI) using the Cough Stimulator device in the inpatient hospital setting for Cough Stimulator implantation and outpatient hospital or residence for follow-up. A neuroprosthesis was implanted for restoration of an effective cough. The annual costs associated with respiratory management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, the subject of this case report did not report incontinence as a concern either before institution of SCS nor afterwards. Moreover, in our previous case series, none of our persons participating in the study of SCS to restore cough reported fecal incontinence associated with SCS [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the subject of this case report did not report incontinence as a concern either before institution of SCS nor afterwards. Moreover, in our previous case series, none of our persons participating in the study of SCS to restore cough reported fecal incontinence associated with SCS [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…O p e n H U B f o r S c i e n t i f i c R e s e a r c h this subject approached 200 cmH 2 O when performed at TLC [3][4][5][6][7][8][9]. Restoration of the ability to generate large intra-abdominal pressures by use of SCS therefore, likely played an important role in the improvements in bowel function observed by this subject.…”
Section: Sci Forschenmentioning
confidence: 92%
See 1 more Smart Citation
“…In a recent cost analysis of the cough system using disc electrodes, we found that the break-even point was achieved within the first year due to the reduction in overall costs of respiratory care. 19 Since placement of wire electrodes can be placed utilizing less surgical time and on an out-patient basis, cost savings with this method could exceed $10,000 resulting in a break-even point well within the first year of use.…”
Section: Discussionmentioning
confidence: 99%